MARKETING RESEARCH: PROBLEM DETERMINATION AND PRACTICE OF QUESTIONNAIRE DEVELOPMENT (CASE OF CONSUMERS RISKS AT THE WINE MARKET) - А. Starostina; V. Kravchenko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The theoretical approach concerns determination of the aim of marketing research has revealed in the article. It allows formalization the analysis of marketing environment factors in a table form, estimation of the basic marketing threats and possibilities of market environment, and clearly formulate aim of marketing research. Process of questionnaire development must be based on strict accordance searching questions, hypothetical variants of answers for searching questions and questions of questionnaire. This process is shown on the example of research of consumers risks at the market of dry wine in Kyiv.